Resizing of Colloidal Gold Nanorods and Morphological Probing by SERS - Fateixa, Sara
We demonstrate that surface-enhanced Raman scattering (SERS) spectroscopy can be used to monitor variations in the aspect ratio (AR) of colloidal gold nanorods (NRs) during a chemical etching process. The AR of colloidal Au NRs prepared by a seed method was deliberately decreased by addition of aqueous K2S2O8. SERS studies using a 1064 nm laser line revealed a decrease on the detection sensitivity as the nanorods became shorter and using the anion diethyldithiocarbamate (DTC) as the analytical probe. The morphological changes observed for distinct reaction times have also been confirmed by TEM and optical measurements. The dependence of the SERS sensitivity observed for Au NRs of variable AR has been investigated either by using colloids submitted to etching at distinct reaction temperatures or by using a distinct excitation laser line. Therefore, this spectroscopic method offers the possibility to probe in situ changes on the AR of colloidal Au NRs in analytical contexts in which other techniques cannot be easily implemented.